Assessment of executive functions in people with Human-Immunodeficiency Virus (HIV) infection using the Behavioural Assessment of the Dysexecutive Syndrome: a pilot study - Campbell, Amanda (2010)
Impairments in executive functions (EF), for example planning and impulsivity, are often identified in people with Human-Immunodeficiency Virus-1 (HIV). Previous research has predominantly used ‘traditional tests’ such as the Stroop, which do not have good ecological validity (Bennett et al., 2005). The main aim of this study was to assess EF in people with HIV using a battery approach with good ecological validity, the Behavioural Assessment of the Dysexecutive Syndrome (BADS) (Wilson et al., 1996). The study used a comparison pilot design to compare performance on the BADS within a sample of participants with HIV to the published normative data. A total of 20 participants with HIV were assessed (13 men; 7 women). On average, participants scored significantly lower on the BADS relative to normative data. Further research should develop the use of neuropsychological batteries with good ecological validity to consider EF impairment in people with HIV. Clinical implications include the potential of EF screening for people with HIV.